Kesejahteraan Karyawan Generasi Z di Era Digital: Peran Strategis Dukungan Sosial - Nita Findias; Nanda Adhi Purusa; Hertiana Ikasari; Febrianur Ibnu Fitroh Sukono Putra (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to examine the impact of work-life balance, job autonomy, effective communication, and social support on employee well-being among Generation Z workers employed at digital agencies in Semarang City. The research background stems from the high workload in the digital creative industry, which can affect the psychological and emotional state of young employees. A quantitative approach is employed via survey method, with data collection conducted through questionnaires distributed to selected respondents based on specific criteria. The sample was determined using purposive sampling technique, yielding 123 respondents qualified for analysis. Data analysis was performed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test the interrelationships among the research variables. The analysis findings reveal that all independent variables—namely work-life balance, job autonomy, effective communication, and social support—exert a positive and significant influence on employee well-being. Among these, social support emerges as the most dominant factor, underscoring the vital role of support from supervisors and colleagues in enhancing the well-being of Generation Z workers. These results also indicate that adequate provision of work resources can sustain and boost employee well-being even amid intense job demands, while offering practical implications for digital agency management and a foundation for future studies.